Peningkatan Hasil Belajar IPAS Melalui Penerapan Metode Demonstrasi pada Peserta Didik Kelas IV SDN 1 Pokak Tahun Pelajaran 2023/2024 - Adnan Maulana Ihsanudin; Tukiyo Tukiyo; Sri Suwartini (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to improve the science and science learning outcomes of class IV students at SDN 1 Pokak academic year 2023/2024. This research uses the Classroom Action Research (PTK) method which uses the Kemmis and Taggart model. The subjects of this research were class IV students at SDN 1 Pokak, totaling 14 participants educate. Data collection techniques through evaluation tests, observation and documentation. The research results show that: (1) students become more active in learning activities. (2) there was an increase in mathematics learning outcomes for class IV students at SDN 1 Pokak. This increase was proven by the results of the pre-cycle test, the class average value was 72.5, then it increased in cycle I to 82.5 and increased again in cycle II to 85.7.